2019
DOI: 10.1021/acs.joc.9b01840
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Catalyzed Rearrangement of 3-Cyanoquinoxalin-2(1H)-ones When Exposed to 1,2-Diaminobenzenes: Synthesis of 2,2′-Bibenzimidazoles

Abstract: A novel and efficient protocol for the synthesis of diversely substituted 2,2′-bibenzimidazoles from the reaction of 3-cyanoquinoxalin-2­(1H)-ones with 1,2-diaminobenzenes has been developed, which proceeds through sequential nucleophilic addition and electrophilic substitution followed by a Mamedov rearrangement. The synthetic utility of this strategy was illustrated by the concise, one-pot synthesis of 5,5′-bi­(2,2′-bibenzimidazoles) and aza-analogues of 2,2′-bibenzimidazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…14 Rearrangement of spirobenzimidazole-2,2′-quinoxalinones D opens up new access to a wide variety of 2,2′-bibenzimidazole derivatives 175. 123 The method allows the introduction of various functional groups at any position of the 2,2′-bibenzimidazoles. As can be seen, this chemistry is not limited to mono-and disubstituted 1,2-DABs 1, a compound with two 1,2-DAB fragments is also an acceptable substrate.…”
Section: Scheme 53mentioning
confidence: 99%
See 1 more Smart Citation
“…14 Rearrangement of spirobenzimidazole-2,2′-quinoxalinones D opens up new access to a wide variety of 2,2′-bibenzimidazole derivatives 175. 123 The method allows the introduction of various functional groups at any position of the 2,2′-bibenzimidazoles. As can be seen, this chemistry is not limited to mono-and disubstituted 1,2-DABs 1, a compound with two 1,2-DAB fragments is also an acceptable substrate.…”
Section: Scheme 53mentioning
confidence: 99%
“…For example, heating quinoxalin-2(1H)-ones 172 at reflux with the 3,3′-diaminobenzidine (173) in AcOH for 7 h yielded the expected 5,5′bi(2,2′-bibenzimidazoles) 176 (Scheme 57). 123 123 The proposed method is characterized by the availability of starting materials, ease of execution, high yields, and a wide range of variable substituents.…”
Section: Scheme 53mentioning
confidence: 99%
“…Next, the loading of catalyst was evaluated and the result revealed that 10% of Cu(PF 6 ) • 4CH 3 CN was suitable for the reaction with the yield of 3 a increasing to 78% (Table 1, entries [12][13]. Subsequently, diverse oxidants including Na 2 S 2 O 8 , PhI(OAc) 2 and PIFA ([Bis (trifluoroacetoxy)iodo]benzene) were also tested again and the results showed that (NH 4 ) 2 S 2 O 8 still was the most appropriate oxidant among the aforementioned oxidants (Table 1, entries [14][15][16]. Finally, several bases (Cs 2 CO 3 , KOAc, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…[4] So, the efficient synthetic means for introduction of sulfonamide groups into (hetero) aromatic rings have received widespread attention and significant achievements in this field have been accomplished in the last several years. [5][6] On the other hand, the direct C3À H bond functionalizations of the quinoxalin-2(1H)-ones have emerged as powerful tools to synthesize complex quinoxalin-2(1H)-one derivatives, [7][8][9][10][11][12][13][14] especially the 3-aminoquinoxalin-2(1H)-one derivatives. The pioneering studies focused on oxidative cross-dehydrogenation coupling of quinoxalin-2(1H)-ones with primary or secondary amines as the nitrogen sources, and Gulevskaya, Cui, Jain or Phan group independently reported the manganese, copper, iodine or copper-organic framework catalytic systems for this transformation (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%